Association between craniocervical dysfunction and temporomandibular disorders young adults - Bautista Carrasco, Aida Melina (2022)
Introduction: The close anatomical and functional relationship involving the cranio-cervico-mandibular system has caused a high prevalence of signs and symptoms of craniocervical dysfunction in subjects with temporomandibular disorder, especially postural and pain problems. Objective: To determine the association between craniocervical dysfunction and Temporomandibular Disorders in young adults. Material and Methods: 180 young adults between 18 and 35 years old were evaluated, distributed in two groups with and without temporomandibular disorder according to Axis I of the Index of Diagnostic Criteria for Temporomandibular Disorders. The first group consisted of 87 students with a diagnosis of temporomandibular disorder and the second of 93 students without this diagnosis. Subsequently, the Craniocervical Dysfunction and Cervical Mobility Index was performed to measure the degree of cervical movement and craniocervical posture. The data were analyzed by descriptive and inferential statistics using the Chi-square test (p = 0.05). Results: Temporomandibular disorders predominated in the female gender (69%). The diagnosis of pain related to temporomandibular disorder predominated for myalgia and arthralgia (38%) and the predominant degree of craniocervical dysfunction was mild (40.4%). Students with mild craniocervical dysfunction presented myalgia (83.3%) and students with severe craniocervical dysfunction presented both (myalgia and arthralgia: 55.6%). Students without temporomandibular disorder had mild craniocervical dysfunction (61.9%) and those with temporomandibular disorder had moderate craniocervical dysfunction (27%). Students with craniocervical dysfunction presented temporomandibular disorder in 64.7%. Conclusions: In this study we found that there was an association between craniocervical dysfunction and temporomandibular disorders in the young adults evaluated.